Short-term pre-exposure to modality mappings: Modality-incompatible single-task exposure reduces modality-specific between-task crosstalk in task-switching - Stephan, Denise Nadine; Fintor, Edina; Koch, Iring (Acta psychologica, 2022)
Modality compatibility refers to the similarity of the stimulus modality and the modality of the sensory-response effect that the response produces (i.e., vocal responses produce auditory effects). In this study, we investigated the effect of short-term pre-exposure of modality compatibility in task-switching. To this end, participants were exposed to either modality-compatible (visual-manual and auditory-vocal) or modality-incompatible (visual-vocal and auditory-manual) single-tasks. After a short-term single-task pre-exposure (with either both modality-compatible tasks, 2 × 80 trials each, or both modality-incompatible tasks, 2 × 80 trials each), participants were transferred to a task-switching situation, where they switched between tasks in both a modality-compatible and an incompatible condition. We found that after pre-exposure to modality-compatible single-tasks the typical effect of modality compatibility was found (i.e., larger switch costs with modality-incompatible tasks compared to modality-compatible tasks). In contrast, after pre-exposed to modality-incompatible single-tasks, modality compatibility no longer influenced switch costs. We assume that long-term modality-compatible associations could be overridden by short-term, task-specific associations to reduce between-task crosstalk. •Modality compatibility: similarity of the stimulus modality and the modality of the sensory-response effect (i.e., vocal-auditory).•Modality compatibility effect persists after short-term pre-exposure with modality compatible single-tasks.•Short-term task specific associations might override long-term modality-compatible ones to reduce between-task crosstalk.